The use of Horizontal Flow Constructed Wetland for Treatment of Sanitary Wastewater in Iraq - Ajell, Azraa Mutasher; Hamza, Zuhal Abdulhadi; Al-Rekabi, Wisam S. (Basrah Journal for Engineering Sciences, 2020)
Constructed wetlands are engineered systems used for wastewater treatment with the objective of reusing water under controlled conditions by mimicking natural treatment mechanisms involving porous media, plants, and microbial communities. This study investigates the performance of a horizontal subsurface flow constructed wetland, where wastewater flows through a gravel bed and vegetation roots, allowing contact with biofilm developed within the wetland substrate. To evaluate treated water quality, physical, chemical, and biological parameters were measured. Field results demonstrated that pollutant removal efficiency increased with detention time. After 3, 4, and 6 days of treatment, average removal efficiencies were 47.7%, 53.2%, and 77.5% for COD; 45.1%, 52.8%, and 64.4% for total nitrogen (TN); and 55.4%, 58.8%, and 72.2% for ammonium (NH₄), respectively. Nitrate removal averaged 19.41% after 3 days. These findings confirm that the horizontal flow constructed wetland system is effective in reducing key wastewater pollutants.